A7.11 IGA autoantigens – a link between the gut and the anti-TNF therapy response in rheumatoid arthritis patients analysed in two independent clinical trials. (13th February 2015) - Konthur, Z; Nonhoff, U; Wiemkes, MM; Detert, J; Braun, T; Hollidt, JM; Burmester, GR; Skriner, K
Abstract : Background: So far no mechanism for non response to biologicals targeting TNFα has been described, despite one third of rheumatoid arthritis patients treated are Non-Responder. A link to the gut microbiota and its ability to drive an autoimmune disease (Immunity. 2010, 32(6):815–27) can be made via segmented filamentous bacteria (SFB) that cooperate to generate potent IgA and Th17 cell responses (Immunity. 2014, 40(4):608–20). We investigated the differences in seroreactivity of patients responding and not responding to anti-TNF therapies prior therapy and identified a diagnostically applicable set of IgA autoantigens to identify non response. Methods: Baseline sera form PREDICT trial treated with Enbrel and patients treated with Humira in the HIT HARD trial (Ann Rheum Dis. 2013, 72(6):844–509) as well as 66 baseline sera from Charité in addition treated with Cimzia and Remicade were investigated on different autoantigens, which were previously identified by protein array screening. The five identified autoantigens (RAB11B, PPP2R1A, KPNB1, COG4, FTFT1) were developed into the pre.mark-TNF ELISA kit by DRDx GmbH. Results: Biologicals-naïve sera from patients diagnosed with RA according to ACR classification criteria, which were initiated on therapy with TNFalpha inhibitors, were analysed with the pre.mark-TNF ELISA kit. In total, analyses of 203 patients were carried out, of which 162 were clearly defined as Responder and 41 clearly defined as Non-Responder after 6 month treatment. 81% of Non-Responder could be clearly identified with the pre.mark-TNF Test. Currently the assay shows a specificity of 94% within this group of 162 Responder. In detail, 80 baseline serum samples from the PREDICT trial (Enbrel) and 57 samples of the HIT HARD (Humira) trial were analysed. In HIT HARD – an early intervention study – all 3 Non-Responder were identified and the specificity of the assay was 98%. In the PREDICT study, Non-Responder were identified with a sensitivity of 69% and a specificity of 93%. Further analysis revealed that the amount of IgA producing B-cells in the synovia differs significantly between patients, while no difference is seen in IgG producing B-cells. Moreover of local TNF-alpha is produced from IgA B-cells in RA synovial tissue and TNFalpha producing macrophages via IgA stimulation. Conclusions: These data suggest that non-response to anti-TNFalpha biologicals might be predicted based on frequency and magnitude of autoantibodies to specific IgA autoantigens. SFB can stimulate IgA production and Th17-cell responses and specific local IgA-producing B-cells might be decisive for disease persistence in TNFalpha inhibitor Non-Responder.